2021
DOI: 10.20546/ijcmas.2021.1001.355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates on Growth and Yield of Indian Mustard (Brassica juncea L.)

Abstract: To study effect of sowing dates on growth and yields of Indian mustard (Brassica junceaL.). Keeping in this view experiment was conducted in Split Plot Design (SPD) with three replications having two factors. First factor comprised of three dates of sowing (15 Oct, 10 Nov. and 05 Dec.) whereas, second factor consist of three Indian mustard varieties viz; Varuna, Narendra rai-1 and Kranti. Results showed that both dates and varieties (10 Nov. and Varuna) superior compare to rest of treatment. However, highest g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Further monthly rainfall distribution pattern during the crop seasons of 16 th October sown crop showed that comparatively higher rainfall was received during November and January commentating vegetative and flowering stage of the crop, however normal rainfall was received during the month of February commentating siliqua formation stage of the crop which helped in terms of increased seed and stover yield. These findings are in close conformity with those of Kumar et al (2017) and Tripathi et al (2021). The 16 th October (24.7) sown crop recorded highest harvest index as compared to 23 th October (23.6) and 30 th October (24.6).…”
Section: Effect Of Date Of Sowingsupporting
confidence: 88%
“…Further monthly rainfall distribution pattern during the crop seasons of 16 th October sown crop showed that comparatively higher rainfall was received during November and January commentating vegetative and flowering stage of the crop, however normal rainfall was received during the month of February commentating siliqua formation stage of the crop which helped in terms of increased seed and stover yield. These findings are in close conformity with those of Kumar et al (2017) and Tripathi et al (2021). The 16 th October (24.7) sown crop recorded highest harvest index as compared to 23 th October (23.6) and 30 th October (24.6).…”
Section: Effect Of Date Of Sowingsupporting
confidence: 88%
“…The results demonstrated that the combined application of humic acid and sulphur significantly increased the weight of Siliqua per plant compared to control groups, across different water regimes. This finding suggests that these amendments play a crucial role in enhancing reproductive development and seed production [23]. Such improvements can contribute to higher crop yields, particularly in areas prone to water variability, thus fostering sustainable agriculture practices [13].…”
Section: Weight Of Siliqua Per Plant (G)mentioning
confidence: 99%
“…With the development of new varieties of crops and the adoption of multiple cropping systems under irrigated conditions, it has become essential to extend its sowing from October to mid-November or even later. Considering the above facts, field experiments were conducted to study the impact of different sowing dates on two commonly grown mustard varieties of mustard in north India [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%